Bioprocessing piping and equipment design : a companion guide for the ASME BPE standard - Huitt, William M., 1943- (Wiley-ASME Press series in Mechanical Engineering, 2017)
Serving as a companion guide to the ASME Bioprocessing Piping and Equipment (BPE) Standard and explaining what lies behind many of the requirements and recommendations within that industry standard, this book shows readers why dimensions and tolerances, process instrumentation, and material selection play such an integral part in the manufacture of components and instrumentation. --